(untitled) (Scientific Researches in Academia, 2024)
This article investigates the multifaceted relationship between digital innovations, children’s rights, and psychological well-being. In an era where digital devices permeate every aspect of daily life, understanding the implications of technology on children’s rights and mental health is paramount. This article explores technology use’s positive and negative impacts on children through a comprehensive analysis. It delves into how digital environments either support or challenge the rights enshrined in the United Nations Convention on the Rights of the Child (CRC), such as access to education, privacy, and protection from harm. Moreover, it examines the psychological effects of technology, ranging from increased connectivity and access to information to concerns over screen addiction, cyberbullying, and exposure to inappropriate content. Drawing upon recent research and case studies, this article offers insights into effective strategies for parents, educators, and policymakers to navigate the digital landscape while safeguarding children’s rights and well-being. By elucidating the complex interplay between digital innovations, children’s rights, and psychological development, this article provides valuable guidance for promoting a balanced and healthy technology integration in children’s lives.